Deep brain stimulation for monogenic Parkinson’s disease: a systematic review - Tomi Kuusimäki; Jaana Korpela; Eero Pekkonen; Mika H. Martikainen; Angelo Antonini; Valtteri Kaasinen (Springer Berlin Heidelberg, 2022)
Deep brain stimulation (DBS) is an effective treatment for Parkinson’s disease (PD) patients with motor fluctuations and dyskinesias. The key DBS efficacy studies were performed in PD patients with unknown genotypes; however, given the estimated monogenic mutation prevalence of approximately 5–10%, most commonly LRRK2, PRKN, PINK1 and SNCA, and risk-increasing genetic factors such as GBA, proper characterization is becoming increasingly relevant. We performed a systematic review of 46 studies that reported DBS effects in 221 genetic PD patients. The results suggest that monogenic PD patients have variable DBS benefit depending on the mutated gene. Outcome appears excellent in patients with the most common LRRK2 mutation, p.G2019S, and good in patients with PRKN mutations but poor in patients with the more rare LRRK2 p.R1441G mutation. The overall benefit of DBS in SNCA, GBA and LRRK2 p.T2031S mutations may be compromised due to rapid progression of cognitive and neuropsychiatric symptoms. In the presence of other mutations, the motor changes in DBS-treated monogenic PD patients appear comparable to those of the general PD population.